2020
DOI: 10.18632/aging.103450
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1 induces cellular senescence and fibrosis in cultured myoblasts. A potential mechanism of aging-related sarcopenia

Abstract: The loss of muscular mass and strength is an inevitable aging related phenomenon, named sarcopenia. The mechanisms involved in its origin and progression remain to be clearly elucidated. Malnutrition, decreased physical exercise and the decline in sex steroid hormone production and in insulin sensitivity play an important role in sarcopenia [1]. Sarcopenic muscles suffer profound changes in their architecture, exhibiting both reduced fiber size and reduced fiber number, especially of the type II fibers, reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 58 publications
1
10
1
Order By: Relevance
“… 66 α-SMA and Fn are universally known and characterized protein used for assessment of fibrosis in several tissues and organs including the kidney and the relative incorporation of the fibrotic markers α-SMA and Fn into the matrix increases in response to TGF-β. 67 , 68 Considering that inflammation-related cytokines and fibrosis-related factors play an important role in the pathological process of MesPGN, we investigated the expression levels of inflammatory chemokine CCL2, TNF-α, IL-6, IL-β1, TGF-β, α-SMA and Fn. We found that the expression levels of the above factors were significantly increased after HSV modeling, indicating that HSV can effectively promote the expression of inflammation and fibrosis factors in nephritis mice, and the MesPGN model was successfully induced by injected HSV twice through tail vein for evaluating the therapeutic effects of DXMS/CAP@PLGA-ILs in MesPGN.…”
Section: Discussionmentioning
confidence: 99%
“… 66 α-SMA and Fn are universally known and characterized protein used for assessment of fibrosis in several tissues and organs including the kidney and the relative incorporation of the fibrotic markers α-SMA and Fn into the matrix increases in response to TGF-β. 67 , 68 Considering that inflammation-related cytokines and fibrosis-related factors play an important role in the pathological process of MesPGN, we investigated the expression levels of inflammatory chemokine CCL2, TNF-α, IL-6, IL-β1, TGF-β, α-SMA and Fn. We found that the expression levels of the above factors were significantly increased after HSV modeling, indicating that HSV can effectively promote the expression of inflammation and fibrosis factors in nephritis mice, and the MesPGN model was successfully induced by injected HSV twice through tail vein for evaluating the therapeutic effects of DXMS/CAP@PLGA-ILs in MesPGN.…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA from endothelial cells or aorta tissue from mice were isolated using Trizol reagent according to the manufacturer’s protocol. cDNA was synthesized using a High Capacity cDNA reverse transcription kit [ 28 , 51 ]. The expressions of IL-1 beta, IL-6, TNF-alfa and MCP-1 in endothelial cells and the expression of endothelial nitric oxide synthase (Nos3), inducible nitric oxide synthase (Nos2), Nrf-2 factor (Nfe2l2), glutathione peroxidase-1 (Gpx1) and superoxide dismutase-2 Mn (Sod2-Mn) in aortas from mice were determined by quantitative PCR (ABI Prism 7500 Fast Real-Time PCR System) and analyzed with 7500 Fast sequence detection software v1.3.1 (Applied Biosystems Inc., Foster City, CA, USA), using specific TaqMan assays and Double delta Ct method.…”
Section: Methodsmentioning
confidence: 99%
“…Recent research has implicated cellular senescence-associated alterations in MuSCs as one of the causative mechanism of age-associated sarcopenia, which may result from loss of muscle regenerative potential. Skeletal muscle has plasticity of regeneration and remodeling due to MuSCs function, and the age-related decline of skeletal muscle mass and function (known as sarcopenia) is associated with loss of MuSCs regenerative capacity with aging ( Sousa-Victor and Munoz-Canoves, 2016 ).Researches about some factors such as endothelin-1, TRIM32, and GSK-3α inducing MuSCs senescence, in which knockout of each of these factors results in muscle degeneration and sarcopenia development, have been carried out in this field ( Kudryashova et al, 2012 ; Zhou et al, 2013 ; Alcalde-Estévez et al, 2020 ). Extrinsic changes and intrinsic changes negatively impact MuSC numbers and functionality, which is particularly pronounced in the sarcopenic muscle of both humans and mice ( Sousa-Victor et al, 2014 ; Wan et al, 2021 ).…”
Section: Mechanisms Of Cellular Senescence In Sarcopeniamentioning
confidence: 99%